Interactive Evaluation of a Music Preprocessing Scheme for Cochlear Implants Based on Spectral Complexity Reduction - Gauer, Johannes; Nagathil, Anil; Martin, Rainer; Thomas, Jan Peter; Völter, Christiane (Frontiers in Neuroscience, 2019)
Music is difficult to access for the majority of CI users as the reduced dynamic range and poor spectral resolution in cochlear implants (CI), amongst others constraints, severely impair the auditory perception. The reduction of spectral complexity is therefore a promising means to facilitate music enjoyment for CI listeners. We evaluate a spectral complexity reduction method for music signals based on principal component analysis that enforces spectral sparsity, emphasizes the melody contour and attenuates interfering accompanying voices. To cover a wide range of spectral complexity reduction levels the design of a new experimental setup for listening experiments was required. It allows CI users to select the preferred level of spectral complexity reduction interactively and in real-time. Ten adult CI recipients with postlingual bilateral profound sensorineural hearing loss and CI experience of at least six months were enrolled in the study. In eight consecutive sessions over a period of four weeks they were asked to choose their preferred version out of ten different complexity settings for a total number of 16 recordings of classical western chamber music pieces. As the experiments were performed in consecutive sessions we also studied a potential long term effect. Therefore, we investigated the hypothesis that repeated engagement with music signals of reduced spectral complexity leads to a habituation effect which allows CI users to deal with music signals of increasing complexity. Questionnaires and tests about music listening habits and musical abilities complemented these experiments. The participants significantly preferred signals with high spectral complexity reduction levels over the unprocessed versions. While the results of earlier studies comprising only two preselected complexity levels were generally confirmed, this study revealed a tendency towards a selection of even higher spectral complexity reduction levels. Therefore, spectral complexity reduction for music signals is a useful strategy to enhance music enjoyment for CI users. Although there is evidence for a habituation effect in some subjects, such an effect has not been significant in general